2016
DOI: 10.37569/dalatuniversity.6.3.81(2016)
|View full text |Cite
|
Sign up to set email alerts
|

The First Report of Pestalotiopsis Sp. Causing Crown Rot Disease on Strawberries in Dalat

Abstract: Nghiên cứu tác nhân gây bệnh khô lá trên giống dâu tây Mỹ Đá (Fragaria x ananassa Duch.) được thực hiện tuân theo các bước của định đề Koch. Kết quả phân lập từ 150 mẫu bộ phận của cây bệnh thu thập từ 3 vùng khác nhau (Phường 7, Phường 8 và Phường 12) tại Đà Lạt thu được 327 mẫu vi sinh vật thuộc 6 loài nấm. Tất cả các mẫu nấm phân lập từ các bộ phận bị bệnh đã được định danh là Pestalotiopsis sp., Verticillium sp., Botrytis cinerea, Cylindrocacpon destructans, Fusarium oxysporum, và Rhizoctonia sp.. Trong đó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…The cultural and morphological characteristics observed in the isolates of Neopestalotiopsis spp. were similar to those described by (Dung et al 2016;Chamorro et al 2016;Essa et al 2018;Sigillo et al 2020), who first reported Neopestalotiopsis spp. as a causal agent of strawberry crown rot in different regions around the world.…”
Section: Discussionsupporting
confidence: 89%
“…The cultural and morphological characteristics observed in the isolates of Neopestalotiopsis spp. were similar to those described by (Dung et al 2016;Chamorro et al 2016;Essa et al 2018;Sigillo et al 2020), who first reported Neopestalotiopsis spp. as a causal agent of strawberry crown rot in different regions around the world.…”
Section: Discussionsupporting
confidence: 89%
“…which proved the Koch's postulate that the disease symptoms were caused by the same fungus that was originally isolated. Similar result was found as previously reported by Dung et al (2016).…”
Section: Pathogenicity Testsupporting
confidence: 93%
“…Diseases are the major constraints in economic production of strawberry. Many pathogen of strawberry have been recorded over the world (Dung et al, 2016). However, crown rot is caused by several pathogens viz., Pestalotiopsis sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Vietnam, Curvularia species such as C. gloeosporioides are known to cause anthracnose disease in coffee [74], and C. lunata causes postharvest problems in rice [75] and dragon fruit [76]. Pestalotiopsis virgatula and P. clavispora were recorded as causal agents of postharvest rot diseases on rambutan [77], and an unidentified Pestalotiopsis was associated with crown rot disease of strawberry [78].…”
Section: Discussionmentioning
confidence: 99%